2021
DOI: 10.1111/jipb.13091
|View full text |Cite
|
Sign up to set email alerts
|

SIZ1 negatively regulates aluminum resistance by mediating the STOP1–ALMT1 pathway in Arabidopsis

Abstract: Sensitive to proton rhizotoxicity 1 (STOP1) functions as a crucial regulator of root growth during aluminum (Al) stress. However, how this transcription factor is regulated by Al stress to affect downstream genes expression is not well understood. To explore the underlying mechanisms of the function and regulation of STOP1, we employed a yeast two hybrid screen to identify STOP1‐interacting proteins. The SUMO E3 ligase SIZ1, was found to interact with STOP1 and mainly facilitate its SUMO modification at K40 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 50 publications
2
31
1
Order By: Relevance
“…They subsequently showed that in protoplasts of the siz1 mutant, recombinant STOP1 is much less sumoylated than in the WT. In a similar assay, Xu et al also observed the reduced sumoylation of STOP1 (Xu et al, 2021).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…They subsequently showed that in protoplasts of the siz1 mutant, recombinant STOP1 is much less sumoylated than in the WT. In a similar assay, Xu et al also observed the reduced sumoylation of STOP1 (Xu et al, 2021).…”
Section: Discussionmentioning
confidence: 80%
“…However, although we verified that the Arabidopsis sumoylation complex proteins were produced and functional in E. coli (on E. coli proteins and on Arabidopsis MYB30), we did not detect any sumoylated forms of STOP1, either with the core machinery alone or after adding SIZ1. Intriguingly, after this study was submitted, an article reporting sumoylated forms of STOP1 using a similar E. coli-based sumoylation assay was published (Xu et al, 2021). These sumoylated forms of STOP1 were observed with the Arabidopsis core sumoylation machinery and without coexpressing SIZ1.…”
Section: Discussionmentioning
confidence: 99%
“…Note: When this paper was accepted and prepared for proof, two groups independently reported that SIZ1 sumoylates STOP1 and that functional disruption of SIZ1 results in overexpression of ALMT1 in Arabidopsis (Fang et al, 2021; Xu et al, 2021). Xu et al (2021) further showed that the PR growth of the double mutant siz1almt1 resembled that of almt1 on ‐Pi medium, indicating that SIZ1 regulates Pi deficiency‐induced inhibition of PR growth by modulating ALMT1 gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…STOP1 is also subjected to SUMO modification through the SUMO E3 ligase SIZ1-dependent and SIZI-independent pathways, and is deSUMOylated by the SUMO proteases EARLY IN SHORT DAYS 4 (ESD4) (Fang et al, 2020(Fang et al, , 2021aXu et al, 2021). The altered levels of STOP1 SUMOylation would affect STOP1 activity and stability, which in turn influences the expression of STOP1-downstream genes and Al resistance (Fang et al, 2020(Fang et al, , 2021aXu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…We recently discovered that F-box proteins REGULATION OF ATALMT1 EXPRESSION 1 (RAE1) and RA E1 H OMOLOG 1 ( RAH1) can facilitate STOP1 ubiquitination and promote its degradation via the ubiquitin-26S proteasome pathway, which is important for balancing Al resistance and plant growth ( Zhang et al, 2019 ; Fang et al, 2021b ). STOP1 is also subjected to SUMO modification through the SUMO E3 ligase SIZ1-dependent and SIZI-independent pathways, and is deSUMOylated by the SUMO proteases EARLY IN SHORT DAYS 4 (ESD4) ( Fang et al, 2020 , 2021a ; Xu et al, 2021 ). The altered levels of STOP1 SUMOylation would affect STOP1 activity and stability, which in turn influences the expression of STOP1-downstream genes and Al resistance ( Fang et al, 2020 , 2021a ; Xu et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%